Halloween animatronics : build a possessed doll - Donat, Wolfram (Great Britain : Amazon, 2013)
We've all seen them: horror movies starring a creepy doll that tries to kill everyone in the house, usually because it's been possessed by a vengeful ghost or a demon. It always starts small, though: little movements, like the head turning, that let you know that something's not quite right about little Samantha's favorite toy. Then, by the end of the movie, the doll is in fully-possessed-mode, flying through the air and slaughtering everyone. Meet Amanda. Amanda is a possessed doll that, with the help of a smattering of code, randomly turns her head left, right, and sometimes all the way around. It's not much, but it's enough to make your favorite horror fan run screaming from the room. Generously illustrated with full-color photographs, this volume of Halloween Animatronics takes you step-by-step through the process of creating her, from cutting open her head to swap out her eyes, to mounting the servo that turns her head, to the few lines of code to make the servo work its magic. If you already have an Arduino, she can be built for under $40 in parts, and an Arduino can be gotten very cheaply if you need one. For those wanting to create spooky Halloween props and get introduced to animatronics, the Arduino, and robotics in general, this book is a must-have!
Keywords: Robotics; Halloween decorations